A new species of Brethesiamyia Maia (Diptera: Cecidomyiidae) from Colombia with description of immature forms - Ospina-Peñuela, Esau Adenawer; Lamas, Carlos José Einicker; Serna, Francisco; Urso-Guimarães, Maria Virginia (Papéis Avulsos de Zoologia, 2020)
A new species of Brethesiamyia (Diptera: Cecidomyiidae) is described from Colombia, which represents the first record of the genus for the country. We described the species based on male, female, pupa, larva of third instar and gall morphology, which the larva induces on leaves of Myrcia sp. (Myrtaceae) from the foothills situated at the connection of the Andes and the Amazon basin from Colombia. The first description of the third larval instar is provided for the genus.